2018
DOI: 10.3174/ajnr.a5530
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of MR Imaging and Dual-Energy CT for the Evaluation of Cartilage Invasion by Laryngeal and Hypopharyngeal Squamous Cell Carcinoma

Abstract: Dual-energy CT showed higher specificity and acceptable sensitivity in diagnosing laryngeal cartilage invasion compared with MR imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(30 citation statements)
references
References 38 publications
2
28
0
Order By: Relevance
“…W e appreciate Dr Ginsberg's interest and comments on our article, "Comparison of MR Imaging and Dual-Energy CT for the Evaluation of Cartilage Invasion by Laryngeal and Hypopharyngeal Squamous Cell Carcinoma." 1 We agree that the hypopharyngeal cancer case (presented in Fig 1) demonstrated lateral extralaryngeal tumor extension through wrapping around the posterior border of the thyroid cartilage on both MR imaging and dual-energy CT. Therefore, this case was defined as T4a disease, regardless of the cartilage invasion finding.…”
supporting
confidence: 74%
See 1 more Smart Citation
“…W e appreciate Dr Ginsberg's interest and comments on our article, "Comparison of MR Imaging and Dual-Energy CT for the Evaluation of Cartilage Invasion by Laryngeal and Hypopharyngeal Squamous Cell Carcinoma." 1 We agree that the hypopharyngeal cancer case (presented in Fig 1) demonstrated lateral extralaryngeal tumor extension through wrapping around the posterior border of the thyroid cartilage on both MR imaging and dual-energy CT. Therefore, this case was defined as T4a disease, regardless of the cartilage invasion finding.…”
supporting
confidence: 74%
“…In our study, extralaryngeal tumor extension was confirmed pathologically in 34 of 55 (62%) patients with advanced hypopharyngeal and laryngeal cancers; however, only 17 of 34 (50%) patients demonstrated cartilage invasion. 1 Extralaryngeal spread can be reasonably well identified on conventional CT, dualenergy CT, 5 and MR imaging; however, extralaryngeal spread "with cartilage invasion" is sometimes overdiagnosed using conventional CT and MR imaging. [5][6][7] As Dr Ginsberg has mentioned concerning laryngeal cancer, tumor erosion limited to the inner cortex of the thyroid cartilage indicates a T3 lesion, whereas erosion of the outer cortex of the thyroid cartilage defines a T4a tumor.…”
mentioning
confidence: 99%
“…In addition, although spatial resolution of CT allows detection of subtle anomalies of the cortical bone of ossified cartilages, bone marrow alterations are difficult to spot and the diagnostic value of ancillary findings, like arytenoid sclerosis, is limited [9]. This may be improved by dual-energy CT, but the sensitivity remains low compared to MR [10,11]. …”
Section: Discussionmentioning
confidence: 99%
“…At present, conventional imaging modalities, for example computed tomography (CT) and magnetic resonance imaging (MRI), play an essential role in the diagnosis of thyroid cartilage invasion [9]. According to the literature, the sensitivity of conventional CT in the diagnosis of thyroid cartilage invasion is low (49-71%) because of the great variability of ossification in the thyroid cartilage [10,11]. The introduction of dual-energy CT has improved the sensitivity of CT to 89% [10,12].…”
Section: Introductionmentioning
confidence: 99%
“…According to the literature, the sensitivity of conventional CT in the diagnosis of thyroid cartilage invasion is low (49-71%) because of the great variability of ossification in the thyroid cartilage [10,11]. The introduction of dual-energy CT has improved the sensitivity of CT to 89% [10,12]. However, dual-energy or spectral CT is expensive and not all hospitals can afford the technology.…”
Section: Introductionmentioning
confidence: 99%